(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Among the "world" languages as a means of international communication, the role of the Russian language is extremely great. The Russian language is rightfully considered the world language, which is due to the entire course of the socio political, economic, scientific, technical and cultural devel opment of mankind in the XX XXI centuries. The role of the Russian language as an international language is also great for the exchange of scientific information. This is primarily due to the "international" nature of modern science and the unprecedented p ace of its development. It is now important that every student speaks fluent Russian. In this regard, it is important to use new methods of teaching the Russian language. The article outlines the methodology of teaching the Russian language in the world ex perience.